Preschool HABIT-ILE: study protocol for a randomised controlled trial to determine efficacy of intensive rehabilitation compared with usual care to improve motor skills of children, aged 2–5 years, with bilateral cerebral palsy. Issue 3 (2nd March 2021) - Sakzewski, Leanne; Reedman, Sarah; McLeod, Kate; Thorley, Megan; Burgess, Andrea; Trost, Stewart; Ahmadi, Matthew; Rowell, David; Chatfield, Mark; Bleyenheuft, Yannick; Boyd, Roslyn N
Abstract : Introduction: Young children with bilateral cerebral palsy (BCP) often experience difficulties with gross motor function, manual ability and posture, impacting developing independence in daily life activities, participation and quality of life. Hand Arm Bimanual Intensive Training Including Lower Extremity (HABIT-ILE) is a novel intensive motor intervention integrating upper and lower extremity training that has been developed and tested in older school-aged children with unilateral and BCP. This study aims to compare an adapted preschool version of HABIT-ILE to usual care in a randomised controlled trial. Methods and analysis: 60 children with BCP aged 2–5 years, Gross Motor Function Classification System (GMFCS) II–IV will be recruited. Children will be stratified by GMFCS and randomised using concealed allocation to either receive Preschool HABIT-ILE or usual care. Preschool HABIT-ILE will be delivered in groups of four to six children, for 3 hours/day for 10 days (total 30 hours). Children receiving Preschool HABIT-ILE be provided a written home programme with the aim of achieving an additional 10 hours of home practice (total dose 40 hours). Outcomes will be assessed at baseline, immediately following intervention and then retention of effects will be tested at 26 weeks. The primary outcome will be the Peabody Developmental Motors Scales–Second Edition to evaluate gross and fine motor skills. Secondary outcomes will be gross motor function (Gross Motor Function Measure-66), bimanual hand performance (Both Hands Assessment), self-care and mobility (Pediatric Evaluation of Disability Inventory-Computer Adapted Test), goal attainment (Canadian Occupational Performance Measure), global performance of daily activities (ACTIVLIM-CP), cognition and adaptive function (Behavior Rating Inventory of Executive Function—Preschool Version), habitual physical activity (ActiGraph GT3X+) and quality of life (Infant Toddler Quality of Life Questionnaire and Child Health Utility Index-9). Analyses will follow standard principles for RCTs using two-group comparisons on all participants on an intention-to-treat basis. Comparisons between groups for primary and secondary outcomes will be conducted using regression models. Ethics and dissemination: Ethics approval has been granted by the Medical Research Ethics Committee Children's Health Queensland Hospital and Health Service Human Research Ethics Committee (HREC/19/QCHQ/59444) and The University of Queensland (2020000336/HREC/19/QCHQ/59444). Trial registration number: ACTRN126200000719.